What does it mean to be youth-friendly? Results from qualitative interviews with health care providers and clinic staff serving youth and young adults living with HIV - Saberi P; Ming K; Dawson-Rose C (Dove Medical Press, 2018)
Parya Saberi,1 Kristin Ming,1 Carol Dawson-Rose2 1Department of Medicine, University of California, San Francisco, San Francisco, CA, USA; 2Department of Community Health Systems, School of Nursing, University of California, San Francisco, San Francisco, CA, USA Purpose: Given the consistent associations between younger age and numerous suboptimal clinical outcomes, there is a critical need for more research in youth living with human immunodeficiency virus (YLWH) and tailoring of health care delivery to the unique and complex needs of this population. The objective of this study was to examine the facilitators of and barriers to engagement in care among YLHW at the system and provider/staff level, as well as the barriers to using technology-based forms of communication with YLWH to improve retention and engagement in care. Patients and methods: We conducted in-depth qualitative interviews with health care providers and staff members at the clinics and organizations serving YLWH in the San Francisco Bay Area. Results: We interviewed 17 health care providers and staff members with a mean of 8 years of experience in providing clinical care to YLWH. Interviewees noted various facilitators of and barriers to engagement in care among YLWH, including the environment of the clinic (e.g., clinic location and service setting), provision of youth-friendly services (e.g., flexible hours and use of technology), and youth-friendly providers/staff (e.g., nonjudgmental approach). With regard to barriers to using technology in organizations and clinics, interviewees discussed the challenges at the system level (e.g., availability of technology, clinic capacity, and Health Insurance Portability and Accountability Act compliance), provider/staff level (e.g., time constraints and familiarity with technology), and youth level (e.g., changing of cellular telephones and relationship with provider/staff). Conclusion: Given the need for improved clinical outcomes among YLWH, our results can provide guidance for clinics and institutions providing care for this population to enhance the youth-friendliness of their services and examine their guidelines around the use of technology. Keywords: HIV, youth, young adults, health care provider, technology, barriers